Chemically Cross-Linked Poly(acrylic-co-vinylsulfonic) Acid Hydrogel for the Delivery of Isosorbide Mononitrate - Talib Hussain; Mahvash Ansari; Nazar Muhammad Ranjha; Ikram Ullah Khan; Yasser Shahzad (The Scientific World Journal)
We report synthesis, characterization, and drug release attributes of a series of novel pH-sensitive poly(acrylic-co-vinylsulfonic) acid hydrogels. These hydrogels were prepared by employing free radical polymerization using ethylene glycol dimethacrylate (EGDMA) and benzyl peroxide (BPO) as cross-linker and initiator, respectively. Effect of acrylic acid (AA), polyvinylsulfonic acid (PVSA), and EGDMA on prepared hydrogels was investigated. All formulations showed higher swelling at high pHs and vice versa. Formulations containing higher content of AA and EGDMA show reduced swelling, but one with higher content of PVSA showed increased swelling. Hydrogel network was characterized by determining structural parameters and loaded with isosorbide mononitrate. FTIR confirmed absence of drug polymer interaction while DSC and TGA demonstrated molecular dispersion of drug in a thermally stable polymeric network. All the hydrogel formulations exhibited a pH dependent release of isosorbide mononitrate which was found to be directly proportional to pH of the medium and PVSA content and inversely proportional to the AA contents. Drug release data were fitted to various kinetics models. Results indicated that release of isosorbide mononitrate from poly(AA-co-VSA) hydrogels was non-Fickian and that the mechanism was diffusion-controlled.